(untitled) (Archives of Clinical Psychiatry, 2007)
BACKGROUND: Schizophrenia is one of the most intriguing and studied psychiatric diseases and its physiopathology has advanced a lot in the last century. OBJECTIVE: To review the most important advances in the physiopathology of schizophrenia. METHOD: Review of the literature of each proposed topic by articles searched in Medline and/or chosen accordingly the authors experience. RESULTS: The dopaminergic hypothesis was one of the first ethiological theories and until today is among the ones that presents the most consistent evidences. However, it fails to explain important features found in schizophrenia, such as the natural history, the cognitive impairments and the structural abnormalities. Evidences provided by epidemiological studies of genetic and environmental risk factors, associated with the findings of neuropathological and neuroimaging studies, suggest an interactive model with several factors acting together to create a global alteration of the brain development. CONCLUSION: The physiophatology of schizophrenia has advanced a lot in the last century, evolving from unicausal theories towards more complex models that consider the interaction among several genetic and environmental factors.